HIFZ AL-MAL SEBAGAI DASAR ETIK-MORAL DALAM MENEKAN ANGKA KEMISKINAN DI INDONESIA - Sanuri . (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
This research focuses on the issue of poverty in Indonesia and the principle of hifz al-mal as its ethical-moral basis. Survey shows that for many years the poverty rate in Indonesia has a tendency to increase although the percentage has a shrinking trend. Many things can be factors of poverty such as; lack of human resources, low natural resources management, weak competitiveness of the education level, jobless, and some others. Starting from these conditions, this paper comes to present information about the Human Development Index rank of either in Southeast Asia and International level. In addition, this study also offers an alternative solution through a concept hifz al-malÂ (maintaining the property) within the meaning of al-tanmiyyah al-iqtisadiyyah (economic development). It is as the ethical-moral basis in reducing poverty in Indonesia through a search of universal values and indicators of each feature of daruriyyat al-khamsah to address some of the key issues in accordance with the assessment criteria to Human Development Index (HDI).